Antecedents of the use of online banking by students in Malaysia: extended TAM validated through SEM - Jan, Muhammad Tahir; Haque, A. K. M. Ahasanul (Medwell Journals, 2014)
The radical advances in the electronic banking technologies have inaugurated unique methods of transaction with a bank, especially using online banking medium. The main purpose of this study is to replicate an extended Technology Acceptance Model (TAM) in order to determine those factors that impact the students’ intention to use online banking, in Malaysian context. The 2 main banks were selected for data collection purposes, namely, Bank Muamalat Malaysia Berhad and Bank Isla